Krugman vs Garicano: Individual and Cultural Differences in the Rhetoric of two Economic Op-ed Writers - Llopis, María Ángeles Orts (HERMES - Journal of Language and Communication in Business, 2016)
The present paper attempts to account for the rhetorical traits of two prestigious economists, who are also authors of economic op-eds: Paul Krugman and Luis Garicano, who write for a prestigious American newspaper, the New York Times, and for the renowned Spanish newspaper, El País, respectively. Through a contrastive study of a roughly 12-thousand-word corpus of either author, this analysis has attempted, on the one hand, to endeavor a qualitative analysis scrutinizing the formal, or lexical-semantic aspects, of their prose in terms of technical words, clichés and coinages, as well as the patterns of conceptualization of the metaphors they use to describe the economic crisis that is sweeping the Western world at large. The second part of the analysis has concentrated upon the interpersonality of the texts, at the pragmatic layer of the op-ed genre, thus covering the extra-linguistic context of the texts which have been scrutinized under the umbrella of metadiscourse. These two different, but complementary, levels of analysis have led to the conclusion that the authors’ styles depict two individual ways in which op-eds are written in the economic world, but that their styles also refl ect cultural and linguistic differences in the way columns are viewed in the English and Spanish languages.